Diagnostic criteria for erosive lichen planus affecting the vulva: an international electronic-Delphi consensus exercise - Simpson, R. C.; Thomas, K.S.; Leighton, Paul; Murphy, R. (Wiley, 2013)
Background: There is no defined set of criteria for diagnosing erosive lichen planus affecting the vulva (ELPV) and there is geographical variation in management.